The Utilization of Political Skill as Leverage in Sport Management Research - Pamela L. Perrewé; Gerald R. Ferris (Journal of Applied Sports Management, 2016)
A major advancement in the political skill program of research was the development of a systematically developed and validated scale to measure political skill (i.e., referred to as the Political Skill Inventory), which reflected its four underlying dimensions of social astuteness, interpersonal influence, networking ability, and apparent sincerity. Also contributing to this expanded program of research was the publication of a comprehensive theoretical statement explaining the process dynamics and operation of the construct (Ferris et al., 2007), and also an applied book on political skill (Ferris, Davidson, & Perrewé, 2005), which discussed the implications for practice of this construct, and how political skill could be trained and developed. This work also provided a specific definition of political skill as “The ability to effectively understand others at work and to use such knowledge to influence others to act in ways that enhance one’s personal and/or organizational objectives” (Ferris et al., 2005, p. 127). This paper examines the utility of using the political skill construct in sport research.
Keywords: political skill; sport research; influence